A Correlation Study of Birthing Ball Technique and Sacral Massage on Maternal and Fetal Well-being Among Parturient Women: A Non-Randomized Clinical Trail - Sundaram Madavan; Bhuvaneswari Gopalakrishnan; Chandrika Anand; Thenmozhi (Journal of Pharmacy and Bioallied Sciences)
Background: A woman’s pregnancy might be challenging because there are so many changes happening at the time. Most women who give birth have severe labor pain. Women typically use a number of coping strategies, including both pharmaceutical and non-pharmacological, or more natural, techniques, to minimize labor discomfort. “Non-pharmacological coping strategies” refers to methods other than using medications to alleviate labor pain. Objective: The present study was conducted to correlate birthing ball exercise and sacral massage on maternal and fetal well-being among prim parturient women Methods: A quasi-experimental design was adopted. A total of 300 primigravidae with 150 each in the experimental and control groups were selected by purposive sampling. Primigravidae in the experiment group underwent birthing ball exercises and sacral massage during their active phase of labor. The control group received routine hospital standard care. The Visual Analog Pain Scale, GAD-7 Anxiety Severity Scale, Apgar score, and Rating scale on Satisfaction were used to collect the data. Descriptive and inferential statistics were used to analyze the collected data. Results: The findings of the study showed that the mutual correlation coefficients of the level of satisfaction, pain perception, anxiety, cervical dilatation, uterine contraction, and fetal heart rate of the control group post-test-2 are given. Conclusion: As a non-pharmacological intervention, the birthing ball technique and sacral massage are necessary to decrease pain perception and reduce anxiety level, which will increase cervical dilatation.